2008
DOI: 10.1007/s00056-008-0735-4
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Facial Profiles as Rated by Individuals with Different Levels of Education

Abstract: The straight-average face was perceived as being the most attractive by representative populations in Germany. On the whole, the university graduates were more critical in their ratings than non-graduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Some studies report that variables such as the rater's gender, 13,[36][37][38] age, [36][37][38] education, 36,39,40 self-perceived attractiveness, 30 proficiency, 13,37,38 and personal profile 36 are influential in the scores of attractiveness. The results of this study reflect the preferences of the raters, who comprised nonprofessional low-and middle-class adult Anatolian Turks who had not received any prior orthodontic treatment and who were high school and university graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that variables such as the rater's gender, 13,[36][37][38] age, [36][37][38] education, 36,39,40 self-perceived attractiveness, 30 proficiency, 13,37,38 and personal profile 36 are influential in the scores of attractiveness. The results of this study reflect the preferences of the raters, who comprised nonprofessional low-and middle-class adult Anatolian Turks who had not received any prior orthodontic treatment and who were high school and university graduates.…”
Section: Discussionmentioning
confidence: 99%
“…The residual variances for the attractiveness and severity test‐retest calculations were 0.389 and 0.316, respectively. A review of the literature found a number of articles that used the 10‐point scale to measure attractiveness, suggesting it is an accepted measure of attractiveness 11–18. We tested the validity of our survey and severity scale.…”
Section: Methodsmentioning
confidence: 99%
“…Unklarheit besteht allerdings immer noch darüber, ob und inwiefern sich die Extraktionstherapie negativ auf das Gesichtsprofil auswirkt. Auch die Attraktivität des Gesichtsprofils ist in zahlreichen Studien [1,9,16,17] with Class II elastics to create neutroclusion. Headgear or other functional orthodontic appliances were not used.…”
Section: Methodsunclassified
“…Yet uncertainty remains regarding whether and if so, to what extent extraction therapy negatively affects the facial profile. The facial profile's attractiveness has also been addressed in numerous studies [1,9,16,17].…”
Section: Introductionmentioning
confidence: 99%